Proses Pengembangan Daya Kritis Mahasiswa dalam Mata Kuliah Nihonjijou Melalui Pembelajaran Berbasis Proyek - Diner, Lispridona (Journal of Japanese Language Education and Linguistics, 2020)
Introducing Japanese culture to Japanese language learners is expected to increase their interest in learning Japanese. Getting to know Japanese culture can also come from other lectures such as kaiwa, dokkai, chokai. Learning Japanese culture has been good so far, namely using two-class activities, "wakaru" and "tanoshii" activities. From the above facts, the researchers practiced different activities from previously that was project-based learning. The purpose of this research is Japanese learning through project-based learning to create an independent learning process, and students can have critical thinking. The research method used descriptive qualitative method. The population and sample of this study were 32 first semester students in the 2019/2020 school year who attended nihonjijo lectures. Data collection techniques used were observation and questionnaires. The observations showed that students could think critically. In essence, there is a "ninja" theme not in the cultural, creative sphere: There are no pictures or the same topics that students choose and are independent: get preliminary information from various sources in completing the learning project. The results of the questionnaire showed that nihonjijo learning through project-based learning 94% of students taking nihonjijo project-based lectures could make students express critical thinking through the delivery of ideas and ideas in groups and 100% could learn independently.